2019
DOI: 10.1016/j.immuni.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Negative Co-stimulation Constrains T Cell Differentiation by Imposing Boundaries on Possible Cell States

Abstract: Graphical AbstractHighlights d Negative co-stimulation limits T cell differentiation outcomes d Archetypal analysis identifies phenotypic boundaries of cell states d CTLA-4 imposes major boundaries on CD4 + T cell phenotypes d PD-1 subtly restrains CD8 + T cell phenotypes Negative co-stimulation is a critical regulator of T cell activity. Wei et al. characterize T cells arising in CTLA-4and PD-1-deficient mice via masscytometry and computational approaches. They show that these negative co-stimulatory molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 90 publications
3
44
0
Order By: Relevance
“…Lastly, studies have also implicated the possibility for CTLA‐4 negative co‐stimulation in the regulation of tonic signals. Knockout of CTLA‐4 in mice leads to aberrant T cell differentiation, indicated by the presence of non‐canonical CD4 + T helper cell subtypes only in the knockout mice . Intriguingly, data from this study illustrate the possibility that CTLA‐4 restricts tonic signaling by raising the threshold for differentiation of promiscuous clones.…”
Section: Outlook: Tonic Signals and Cancer Immunotherapy?mentioning
confidence: 66%
See 1 more Smart Citation
“…Lastly, studies have also implicated the possibility for CTLA‐4 negative co‐stimulation in the regulation of tonic signals. Knockout of CTLA‐4 in mice leads to aberrant T cell differentiation, indicated by the presence of non‐canonical CD4 + T helper cell subtypes only in the knockout mice . Intriguingly, data from this study illustrate the possibility that CTLA‐4 restricts tonic signaling by raising the threshold for differentiation of promiscuous clones.…”
Section: Outlook: Tonic Signals and Cancer Immunotherapy?mentioning
confidence: 66%
“…Intriguingly, data from this study illustrate the possibility that CTLA‐4 restricts tonic signaling by raising the threshold for differentiation of promiscuous clones. T cells from CTLA‐4 deficient mice may be more responsive to self‐antigens as well, as CTLA‐4 deletion was correlated with decreased N region insertions, which can contribute to self‐reactivity . How exactly CTLA‐4 may receive or transduce tonic signals remains to be defined, but these recent data provide an important starting point.…”
Section: Outlook: Tonic Signals and Cancer Immunotherapy?mentioning
confidence: 99%
“…Th17 cells display a molecular signature consistent with stem-like properties, can give rise to Th1-like cells while also self-renewing to maintain a population of IL-17A-secreting cells, and demonstrate increased antitumor potency over Th1 cells when adoptively transferred in mouse models of melanoma (66,67). In the absence of negative costimulation by CTLA4 or after anti-CTLA4 antibody blockade, CD4 + T cells can differentiate into an ICOS + Th1-skewed population with superphysiological cytokine output capabilities (68). On a molecular level, these results suggest that the ICOS YMFM motif is at least in part responsible for CD4 + T cell differentiation toward a Th17 phenotype.…”
Section: Methodsmentioning
confidence: 94%
“…Another study 42 suggests the survival of subdominant CD8 + T cell clones is usually negatively affected by immunodominant clones; however, PD-1 blockade inhibits this effect thus enhancing survival and population size. In another study, 43 CTLA-4 knockout mice had increased T cell clonality in the lymph node, while Karandikar et al 44 showed that CTLA-4 blockade during the acute phase of experimental autoimmune encephalomyelitis leads to enhanced epitope spreading. Both of these studies suggest that the T cell clonality mechanism was due to CTLA-4 being a natural inhibitor of self-reactive or subdominant clones and that blocking CTLA-4 lowers the threshold for activation of both clonotypes.…”
Section: Discussionmentioning
confidence: 98%